Reaction of condensed cyclohexane isoxazolones with Grignard rea gents - Vasilyeva Наталья G.; Lakhvich, Fjodor A.; Kozlova-Kozyrevskaya, Alla L. (Journal of the Belarusian State University. Chemistry, 2019)
Synthesis of new 2-acyl derivatives of 1,3-cyclohexanediones, various variants of their subsequent chemical transformation are relevant for organic and bioorganic chemistry, since it is known that a large number of such substances are bioactive. The presence of several reaction centers in this series of compounds makes it difficult to target specifically the carbonyl group or other reaction centers in the reaction. To exclude the competitive course of adverse reactions in the targeted modification of the initial ones, the property of the β-diketone grouping is easily converted to isoxazoles, which are their latent form, which can easily be regenerated at certain stages of the synthetic process from the latter. Stability of the same isoxazole cycle under the conditions of many chemical reactions allows the directed effect on the cyclohexane fragment of molecules or make changes in the side acyl chain. To study the modification of 2-acylcyclohexane-1,3-diones on the cyclic part of the molecule, the Grignard reaction was studied using the cyclohexanoisoxazolones obtained earlier. However, it was not possible to isolate the expected products of 1,2-addition via the carbonyl group. Instead of them, compounds were isolated, to which the structure of alkylidenebenzo[d]isoxazoles was attributed.